Karakteristik Alat Pemanen Madu Tipe Isap dengan Variasi Tekanan Vakum - Sutejo, Agus; Al Khalidhi, M. Alvhandi; Ramdani, Gilang; Putri, Annastasha Diandra (Jurnal Agricultural Biosystem Engineering, 2025)
Honey harvesting is one of the main activities in beekeeping. The honey harvesting process plays a crucial role in ensuring the quality and quantity of the final product. This study aims to analyze the characteristics of suction-type honey harvesting with variations in vacuum pressure to determine the impact of pressure factors on the effectiveness of hive repair, the quality of the honey produced, and the speed of harvesting. The study was conducted from July to September 2024 at PT Daud Teknik Maju Pratama, Agribusiness and Technology Park IPB, and The Animal House, using two different pressures: -23.37 cmHg and -21.34 cmHg. Vacuum pressure honey harvesting proved to be effective as it could be performed quickly without damaging the honeycomb. On the other hand, the pressing method was less effective because it could damage the hive, resulting in a longer time required for bees to repair it. Harvesting 300 ml of honey using pressures of -9.2 cmHg and -8.4 cmHg took approximately 5.4 minutes and 6.72 minutes, respectively. The honey produced showed varying viscosity values, such as honey from Trigona laeviceps in hive 1 with a viscosity of 122.395 mPa.s, hive 5 with a viscosity of 99.645 mPa.s, hive 10 with a viscosity of 121.117 mPa.s, and honey from Trigona itama with a viscosity of 79.346 mPa.s. Keywords: Effectiveness, Honey, Pressure Variation, Vacuum Pump, Viscosity.